Uma arquitetura de sensoriamento social para suporte à comunicação não planejada no contexto de violência urbana no projeto CidadeSocial - Silva, Eliel Roger da; França, Tiago Cruz de; Oliveira, Jonice (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2025)
This research investigated how the concept of social sensing can be used as an approach to support unplanned communication among citizens in the context of urban violence. Also, it researched how to identify and classify severity levels in text messages published on social media about the daily life of a city. As results, two conference papers were published, a undergraduate student supervision was conducted, and a software that implements the proposed architecture was built. The research advanced the capability to democratize access to information in critical contexts, map violence patterns through automatic classification, and strengthen urban resilience by enabling unplanned communication about risk events.